Combined contribution of biochar and introduced AM fungi on lead stability and microbial community in polluted agricultural soil - Chen, Xuedong; Tang, Lin; Wu, Kongyang; Mo, Yifan; Tang, Qian; Li, Gaojie; Zhu, Ying (Frontiers in Microbiology, 2023)
Lead (Pb) pollution in agricultural soil has been accelerated by industrial development and human activities, and poses a major threat to agricultural ecosystems. Both biochar and arbuscular mycorrhiza (AM) fungi are considered to play an important role in remediation of Pb contaminated soil. The combined remediation effects of introduced AM fungi and biochar on soil properties, Pb availability, microbial community and functional profiles were systematically investigated in unsterilized Pb-polluted agricultural soil. Results indicated that soil nutrients were significantly improved through the combined application of biochar and introduced AM fungi. The introduced AM fungi combined with biochar prepared at 400℃ and 500℃ promoted the transformation of Pb to a more stable state with low bioavailability. Moreover, the addition of AM fungi and biochar affected the relative abundances of dominant bacteria and fungi at the phylum and genus levels. Biochar mainly affected soil bacterial community and obviously increased the relative abundance of Actinobacteria and Blastococcus. The interactions between biochar and introduced AM fungi mainly affected fungal community, and increased the abundance of Ascomycota and Botryotrichum. Further, PICRUSt analysis indicated biochar amendment supported stronger bacterial metabolic functional potentials. Therefore, the combined application of biochar and introduced AM fungi could improve soil nutrients, reduce Pb availability, and show a positive effect on indigenous microbial communities and metabolic functions in farmland soil.